Early-Life Home Environment and Obesity in a Mexican American Birth Cohort: The CHAMACOS Study. Issue 2 (February 2019) - Tindula, Gwen; Gunier, Robert B.; Deardorff, Julianna; Nabaglo, Kelly; Hubbard, Alan; Huen, Karen; Eskenazi, Brenda; Holland, Nina
ABSTRACT: Objective: Little is known about the impact of the home environment on biomarkers of obesity, such as adipokines, in children. In this study, we examined the relationship of maternal depressive symptoms and potentially protective social factors, including maternal support and the home learning environment, with body mass index and adipokines. Methods: Data were obtained from 326 Mexican American participants from the Center for the Health Assessment of Mothers and Children of Salinas cohort. Plasma adipokine levels were assessed in 326 children by enzyme-linked immunoassay at birth or ages 5, 9, or 14 years. Maternal depressive symptoms were evaluated using the Center for Epidemiological Studies Depression Scale when children were 1, 3.5, 7, and 9 years old; social support was assessed by the Duke-University of North Carolina Questionnaire at ages 1 and 5 years; and home learning environment by the Home Observation for the Measurement of the Environment (HOME) at ages of 6 months and 1, 2, 3.5, 7, 9, and 10.5 years. Results: Age was significantly associated with adiponectin ( B = −5.0, SE = 0.2) and leptin ( B = 0.01, SE = 0.003) levels. Individual time point analyses identified significant positive associations of HOME scores in childhood with adiponectin at ages 9 years (HOME score; age 3.5 years: B = 0.9, p = .04) and 14 years (HOME score; age 7 years: B = 0.6, p = .02, age 9 years: B = 0.6, p = .05, age 10.5 years: B = 0.5, p = .04). We observed significant relationships of maternal depressive symptoms at age 9 years with adiponectin and body mass index z-score at age 14 years ( B = −0.2, p = .003 and B = 0.02, p = .002, resp.), which were confirmed in longitudinal models. Conclusions: This study adds new evidence that adverse and protective aspects of the home environment could lead to altered obesity status in children. Abstract : Supplemental digital content is available in the text.